Comparison of Blood Platelet Thromboxane A2 in Normal and Diabetic Subjects - Temboonkiat, Supatta; Ketsa-ard, Kanchana (Journal of Basic and Applied Pharmacology, 2015)
The superfusion bioassay of thromboxane A2 (TXA2) in blood platelets of normal subjects, diabetic patients with and without diabetic retinopathy was studied. The patients with diabetic retinopathy were on aspirin for treatment of their retinopathy. The washed platelet suspension was prepared from platelet-rich plasma (PRP). Bioassay of TXA2 in thrombin-treated platelet suspension was carried out using the rabbit aorta superfusion technique at 37°C. Estimated TXA2 was a relative value by assuming the TXA2 level of normal subjects to be 1.00. The diabetics without aspirin treatment had high concentrations of TXA2 (2.27 ± 1.69), while the TXA2 concentration of the diabetics with aspirin-intake was low (0.66 ± 0.40). The relative TXA2 concentrations of normal and diabetic with aspirin-intake groups were significantly different from that of the diabetic without aspirin group (p <0.001). The difference of the relative TXA2 concentrations in normal and diabetic with aspirin-intake groups was also statistically significant (p <0.05). This indicated that diabetic patients tended to have higher concentration of TXA2 than normal subjects and this might be a cause of several vascular complications in diabetes mellitus. In addition, aspirin does reduce the TXA2 concentrations.